Kegiatan Apresiasi Puisi dan Cerpen Karya Siswa untuk Meningkatkan Literasi di SMK Negeri 1 Kepil - Setiyono, Junaedi; Rokhayati, Titi; Hasyim, Wachid (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This community service activity was carried out through collaboration between Muhammadiyah University Purworejo and SMK Negeri 1 Kepil, Wonosobo, with the aim of increasing students' motivation and skills in writing literary works, particularly poetry and short stories. The background to this activity was the common problem faced by high school students and their equivalents, namely limited knowledge, insight, and skills in producing quality literary works. The implementation methods included lectures, question-and-answer sessions, and interactive discussions, with the main content being inspirational narratives about the experience of writing poetry and short stories presented by the speakers. The results of the activity showed the collection of 73 literary works, consisting of 45 poems and 28 short stories, all of which received appreciation through discussions of their strengths and constructive feedback to improve their weaknesses. Students' enthusiasm was reflected in their active participation, both in discussion sessions and in the interlude event featuring poetry readings. This activity also encouraged students to submit their literary works to teachers who also served as committee members, thereby fostering a spirit of continued writing. Overall, this activity made a positive contribution to addressing low motivation to write and limitations in students' knowledge and skills in the field of literature. Furthermore, this programme is expected to become a sustainable catalyst for the creation of a culture of creative literacy in schools, enabling students to develop their literary potential to the fullest.